(untitled) (Journal of Partial Differential Equations, 2018)
We establish conditions of the nonexistence of weak solutions of the Dirichlet problem for nonlinear elliptic equations of arbitrary even order with some righthand sides from L^m where m > 1. The conditions include the requirement of a certain closeness of the parameter m to 1.